Diverse Ligand‐Functionalized Mixed‐Valent Hexamanganese Sandwiched Silicotungstates with Single‐Molecule Magnet Behavior. Issue 35 (4th July 2016) - Xue, Han; Zhao, Jun‐Wei; Pan, Rui; Yang, Bai‐Feng; Yang, Guo‐Yu; Liu, Hong‐Sheng
Abstract: Under hydrothermal conditions, replacement of the water molecules in the [Mn III 4 Mn II 2 O4 (H2 O)4 ] 8+ cluster of mixed‐valent Mn6 sandwiched silicotungstate [(B‐α‐SiW9 O34 )2 Mn III 4 Mn II 2 O4 (H2 O)4 ] 12− (1 a ) with organic N ligands led to the isolation of five organic–inorganic hybrid, Mn6 ‐substituted polyoxometalates (POMs)2 –6 . They were all structurally characterized by IR spectroscopy, elemental analysis, thermogravimetric analysis, diffuse‐reflectance spectroscopy, and powder and single‐crystal X‐ray diffraction. Compounds2 –6 represent the first series of mixed‐valent {Mn III 4 Mn II 2 O4 (H2 O)4− n (L) n } sandwiched POMs covalently functionalized by organic ligands. The preparation of1 –6 not only indicates that the double‐cubane {Mn III 4 Mn II 2 O4 (H2 O)4− n (L) n } clusters are very stable fragments in both conventional aqueous solution and hydrothermal systems and that organic functionalization of the [Mn III 4 Mn II 2 O4 (H2 O)4 ] 8+ cluster by substitution reactions is feasible, but also demonstrates that hydrothermal environments can promote and facilitate the occurrence of this substitution reaction. This work confirms that hydrothermal synthesis is effective for making novel mixed‐valent POMs substituted with transition‐metal (TM) clusters by combining lacunary Keggin precursors with TM cations and tunable organic ligands. Furthermore, magnetic measurements reveal that3 and6 exhibit single‐molecule magnet behavior. Abstract : Organically functionalized polyoxometalates : A series of hexa‐Mn‐substituted sandwich‐type silicotungstates was synthesized hydrothermally by replacement of the water molecules in [(B‐α‐SiW9 O34 )2 Mn III 4 Mn II 2 O4 (H2 O)4 ] 12− organic N ligands (e.g., see figure). They are the first mixed‐valent Mn6 ‐substituted POMs covalently functionalized with organic ligands.